Warehouse management model under the lean warehousing approach to increase the order fill rate in glass marketing SMES - Franco Silvera, Nicole Ariane (2024)
The commercial sector represents 10.6% of the national GDP, and the wholesale or retail trade increased by 17.3% last year; for this reason, the following article is based on the import of glass, this activity has to cope with costs, quality and time, as well as achieving optimal profitability. Therefore, it is important to plan the different stages of the process, the supply of the product, the order in the warehouse, the correct execution of packing and picking. For this reason, the study was carried out in the warehouse area, 5S, standardized work and ABC Multicriteria were proposed to improve the Fill Rate indicator, which is currently at 93.3% due to inadequate management in the warehouse, affecting profits. By implementing the pilot plan and carrying out the simulation in Arena, it was possible to verify the improvement of the proposed model, this raising the Fill Rate indicator to 97.36%.